## Question

### Solution

Correct option is Differentiating the given expression, we get

3x2 – 4xy2 – 4x2yy’ + 5 + y’ = 0

Putting x = 1, we have

3 – 4.1.1 – 4.1.1y’ (1) + 5 + y’(1) = 0

⇒               4 – 3y’(1) = 0 ⇒ y’(1) = 4/3

Differentiating again, we have Putting x – 1, y = 1 and y’(1) = 4/3, we get  #### SIMILAR QUESTIONS

Q1

Given f’(2) = 6 and f’(1) = 4. Q2

Let R âŸ¶ R be such that f(1) = 3 and f’(1) = 6. Then Q3

The domain of the derivative of the function Q4

If (0) = 0, f’(0) = 2 then the derivative of at x = 0 is

Q5 If f is differentiable for all x then

Q6

Let f and g be differentiable function such that f’(x) = 2g(x) and g’(x) = –f(x), and let T(x) = (f (x))2 – (g(x))2. Then T’(x) is equal to

Q7

Let f be a twice differentiable function such that f’’(x) = –f(x) and f’(x) = g(x). If h’(x) = [f(x)]2 + [g(x)]2h(1) = 8 and

h(0) = 2, then h(2) is equal to

Q8

If y2 = P(x) is a polynomial of degree 3, then is equal to

Q9

If then the set of all points where the derivative exist is

Q10

If f(x , then f’(1) equals